Fractional order Proportional-Integral-Derivative Controller parameter selection based on iterative feedback tuning. Case study: Ball Levitation system. (April 2018) - Rezaei Estakhrouiyeh, Mohsen; Gharaveisi, Aliakbar; Vali, Mohammadali
In the present research, Iterative Feedback Tuning (IFT) algorithm is employed to tune a type of fractional order Proportional-Integral-Derivative (PID)( P I α D ) controller. For this purpose, fractional order calculus is introduced and some important principles are represented. Then, IFT algorithm is presented in a general form. Following it, IFT algorithm is derived to tune the specific type of PID. The relevant update law is calculated for the fractional order controller. Finally, the proposed algorithm is tested on a Hardware in Loop (HIL) system, that is, Ball Levitation (BL) system, and the efficiency of the proposed method is verified via experiments.